Beeinflussen Klima-Schulstreiks die politische Agenda?: Eine Analyse der Twitterkommunikation von Bundestagsabgeordneten - Raisch, Judith; Zohlnhöfer, Reimut (Zeitschrift für Parlamentsfragen, 2020)
Have the school strikes for the climate (Fridays for Future (FFF) movement) affected political agenda setting in Germany? And does a MP’s party affiliation matter for how often and in what ways he or she mentions the FFF movement? These questions are answered by analyzing 78,000 Twitter tweets of 89 Members of the German Bundestag from all seven parties represented in parliament between November 2017 und April 2019 . MPs of all parties paid more attention to climate issues after the school strikes began . Moreover, and in line with the expectations of the issue ownership literature, it turns out that MPs for the Greens and the Left Party referred more often to the FFF movement in their tweets than members of the AfD, FDP, CDU, and CSU . Similarly, Green and Left MPs’ tweets about the FFF movement were more positive, encouraged followers to support the movement more often, and linked comments on the FFF movement that critiqued the government’s climate policy more frequently than members of the latter parties . The tweets of SPD MPs resembled those of Green and Left MPs .
Gesehen am 02.03.2021
Keywords: Fridays for Future; Twitter; Abgeordneter; Deutschland / Deutscher Bundestag; Deutschland